School Participation Empowerment Scale (SPES) adaptation for teachers in Malaysia - Mohd Yusoff, Suhaili; Tengku Ariffin, Tengku Faekah; Md Zalli, Mohd Muslim (2020)
Teacher empowerment is increasingly gaining attention among scholars and practitioners across educational contexts due to positive outcomes, especially for school effectiveness in general. Teachers should be empowered to improve their efficiency and professionalism based on their capabilities towards achieving an enhanced teacher workplace and well-being in schools. Therefore, this study validated the measurement model of teacher empowerment as a result of a modification in the School Participation Empowerment Scale (SPES) developed by Short and Rinehart (1992). Three items were removed due to the difference in culture, while 35 of the items were retained and modified. The questionnaires were distributed to 371 respondents using multi-stage sampling. These respondents were secondary school teachers from the state of Kelantan. Confirmatory factor analysis (CFA) in Structural Equation Modelling in AMOS version 24 was employed to assess the fitness of the measurement model. The results showed that fitness indexes achieved the level of acceptance (RMSEA = .066, CFI = .926, TLI = .920, ChiSq / df = 2.611). Therefore, this model is suitable for the teacher empowerment construct. This study hopes to be of use in future research on teacher empowerment that could bring further improvement in school effectiveness.